Verifying digital systems with MATLAB - Chaves, L; Bessa, I; Cordeiro, L; Kroening, D; Lima Filho, E (Association for Computing Machinery, 2017)
A MATLAB toolbox is presented, with the goal of checking occurrences of design errors typically found in fixed-point digital systems, considering finite word-length effects. In particular, the present toolbox works as a front-end to a recently introduced verification tool, known as Digital-System Verifier (DSVerifier), and checks overflow, limit cycle, quantization, stability, and minimum phase errors in digital systems represented by transfer-function and state-space equations. It provides a command-line version with simplified access to specific functionality and a graphical-user interface, which was developed as a MATLAB application. The resulting toolbox enables application of verification to real-world systems by control engineers.